2017
DOI: 10.14260/jemds/2017/954
|View full text |Cite
|
Sign up to set email alerts
|

Pectoral Nerve Block Versus Thoracic Paravertebral Block– Comparison of Analgesic Efficacy for Postoperative Pain Relief in Modified Radical Mastectomy Surgeries

Abstract: BACKGROUNDModified Radical Mastectomy (MRM) is the most common surgical procedure for operable breast malignancies. Postoperative pain has been severe in MRM cases and demands for pain relief are high. The technique of performing pectoral nerve block [PECS] using ultrasound guidance is increasing in popularity. We compared the postoperative analgesic profile of ultrasound-guided serratus plane block (SPB) and landmark-guided paravertebral block (PVB). MATERIALS AND METHODSThis study was done as a double blind,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
1
4
0
2
Order By: Relevance
“…In this study, there was no significant difference in intra- and post-operative haemodynamic parameters between the two groups [Figures 2 and 3 ], which is supported by a similar study where pectoral nerve block and thoracic paravertebral block were compared for mastectomy. [ 17 ] In this study, better haemodynamic stability was observed intraoperatively in Group II. Thus, it can be said that Pecs block has no untoward effect on HR, SBP, DBP and MAP of the patients.…”
Section: Discussionsupporting
confidence: 50%
“…In this study, there was no significant difference in intra- and post-operative haemodynamic parameters between the two groups [Figures 2 and 3 ], which is supported by a similar study where pectoral nerve block and thoracic paravertebral block were compared for mastectomy. [ 17 ] In this study, better haemodynamic stability was observed intraoperatively in Group II. Thus, it can be said that Pecs block has no untoward effect on HR, SBP, DBP and MAP of the patients.…”
Section: Discussionsupporting
confidence: 50%
“…In only one study of Syal et al, which compared fentanyl analgesia in the postoperative period, there was a greater need of opioids in Pecs group, but without statistical significance [8]. The time to first rescue analgesia was longer in the Pecs group and the same results were also observed in other similar studies [7,12,11,13]. In previous studies the time after surgery to the first rescue analgesia varied due to the different plans of postoperative analgesia according to the study design.…”
Section: Resultsmentioning
confidence: 74%
“…In the study we compared the analgesic effects of two thoracic wall nerve blocks, as TPVB is well-researched and effective method and Pecs block may be no less effective, but currently has a smaller evidence base. In this study the paravertebral block was performed at only one Th 3-4 level, as well as in most previous researches, which compared the efficacy of these two techniques [7,11,12,13]. Although there is evidence that analgesic effect is better when the paravertebral block is performed at several levels [14].…”
Section: Resultsmentioning
confidence: 87%
“…[27]. Подібні результати при порівнянні застосування цих двох блокад для знеболювання мастектомії у 60 пацієнток отримав G. Annamalai та співавт., де частота ПОНБ становила в групі ПБ 16,7 %, а в групі ПВБ -30 % [28]. Хоча в рандомізованому проспективному дослідженні S.S. Wahba та співавт., де були включені пацієнти після мастектомії, не виявили статистично вірогідної різниці в частоті ПОНБ між ПБ і ПВБ [9].…”
Section: таблиця 2 знеболювання активізація прийом їжі та понб після різних видів анестезіїunclassified
“…Дане дослідження має низку обмежень. У дослідженні виконували паравертебральний блок лише на одному рівні Тh3-4, як і в більшості попередніх робіт, де порівнювали ефективність цих двох технік [9,19,27,28]. Хоча знеболювальний ефект кращий, якщо паравертебральну блокаду виконувати на декількох рівнях [29].…”
Section: таблиця 2 знеболювання активізація прийом їжі та понб після різних видів анестезіїunclassified